Remote experimentation network - yielding an inter-university peer-to-peer e-service - Gustavo R. Alves (2005)
The goal of this paper is to discuss the benefits and challenges of yielding an inter-continental network of remote laboratories supported and used by both European and Latin American Institutions of Higher Education. Since remote experimentation, understood as the ability to carry out real-world experiments through a simple web browser, is already a proven solution for the educational community as a supplement to on-site practical lab work (and in some cases, namely for distance learning courses, a replacement to that work), the purpose is not to discuss its technical, pedagogical, or economical strengths, but rather to raise and try to answer some questions about the underlying benefits and challenges of establishing a peer-to-peer network of remote labs. Ultimately, we regard such a network as a constructive mechanism to help students gain the working and social skills often valued by multinational/global companies, while also providing awareness of local cultural aspects.